2014
DOI: 10.1021/ac503142u
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Ion Mobility Mass Spectrometry for Isomer Composition Determination Extracted from Se-Rich Yeast

Abstract: The isomer ratio determination of a selenium-containing metabolite produced by Se-rich yeast was performed. Electrospray ionization and ion mobility mass spectrometry (IM-MS) were unsuccessfully used in order to resolve the isomers according to their collisional cross section (CCS) difference. The isomer ratio determination of 2,3-dihydroxypropionylselenocystathionine was performed after multidimensional liquid chromatography preconcentration from a water extract of Se-rich yeast using preparative size exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The separation mechanism in these experiments was similar to those studied in this review in that they encompass the selective change in the ions' CCSs. However, the crown ethers were injected in the aqueous phase previous to IMS‐MS, not in the buffer gas, and the clusters did not establish equilibria in the buffer gas because the cluster formation was irreversible due to the strong ion‐SR interaction.…”
Section: Applications Of Mobility Shifts Upon Injection Of Buffer Gasmentioning
confidence: 69%
See 2 more Smart Citations
“…The separation mechanism in these experiments was similar to those studied in this review in that they encompass the selective change in the ions' CCSs. However, the crown ethers were injected in the aqueous phase previous to IMS‐MS, not in the buffer gas, and the clusters did not establish equilibria in the buffer gas because the cluster formation was irreversible due to the strong ion‐SR interaction.…”
Section: Applications Of Mobility Shifts Upon Injection Of Buffer Gasmentioning
confidence: 69%
“…This methodology is advantageous in that the buffer gas is saturated with the SRs leading to equilibria between analyte ions and SR molecules producing clear and sharp peaks of analyte ion‐SR clusters.In other application, the isomer ratio determination of a selenium‐containing metabolite was performed after multidimensional liquid chromatography preconcentration from a yeast water extract. An SR, 4′‐nitrobenzo‐15‐crown‐5 ether, was added to the ESI solution to increase the CCS of one of the isomers by the formation of a stable host–guest system and separate the isomers . Kune et al also used crown ethers as SRs in IMS to separate valine and proline protonated ions because the crown ethers were selective to the primary amino group in valine, absent in proline, decreasing valine's mobility:
…”
Section: Applications Of Mobility Shifts Upon Injection Of Buffer Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…An SR is a modifier additive that changes the CCS of a target ion by the formation of host‐guest systems and leading to a shift in the ion mobility coefficient (generally to lower values). SR can be used as a drift gas modifier in the IMS cell or as a complexing agent (i. e. a ligand) in solution added before the sample injection . In addition to avoiding false positives, the use of SR could also increase the confidence level of ion detection by checking the ion mobility values of the target ion before and after coordination with the SR. For instance, one of the well‐known SR is the 18‐crown‐6 ether.…”
Section: Introductionmentioning
confidence: 99%
“…Paglia and coworkers demonstrated the utility of incorporating such mobility information into comparative metabolomics workflows and described searchable collision cross section databases to aid ion identification. 40 One recent study used the structural heterogeneity of phosphorylated peptide ions doped into tryptic digests to link precursor ions with those formed upon neutral loss of H 3 PO 4 resulting from collisional activation at the back of the drift tube. 37 Similarly, experiments recently showed that mobility measurements could be used with other analytical information (LC retention time and precursor and fragment ion masses) to distinguish isomeric species in complex mixtures obtained from natural products 38 as well as to identify potential biomarkers in comparative metabolomics analyses 39 .…”
mentioning
confidence: 99%